Gas seepage equation of deep mined coal seams and its application - HU, Guo-zhong; WANG, Hong-tu; TAN, Hai-xiang; FAN, Xiao-gang; YUAN, Zhi-gang (Journal of China University of Mining and Technology, 2008)
In order to obtain a gas seepage law of deep mined coal seams, according to the properties of coalbed methane seepage in in-situ stress and geothermal temperature fields, the gas seepage equation of deep mined coal seams with the Klinkenberg effect was obtained by confirming the coatbed methane permeability in in-situ stress and geothermal temperature fields. Aimed at the condition in which the coal seams have or do not have an outcrop and outlet on the ground, the application of the gas seepage equation of deep mined coal seams in in-situ stress and geothermal temperature fields on the gas pressure calculation of deep mined coal seams was investigated. The comparison between calculated and measured results indicates that the calculation method of gas pressure, based on the gas seepage equation of deep mined coal seams in in-situ stress and geothermal temperature fields can accu- rately be identical with the measured values and theoretically perfect the calculation method of gas pressure of deep mined coal seams.